BIG DATA AND BUSINESS INTELLIGENCE: their differences and importance for organizations - REGINA RODRIGUES, CARLA; Sotto, Eder Carlos Salazar (Revista Interface Tecnológica, 2022)
When entering the business world currently, several techniques and tools are used in the corporate area to assist and improve management, dealing with data, in order to facilitate and improve the flow of this information, one of which is Big Data. and Business Intelligence, that many people still confuse these terms, both in their definitions and in their objectives, because of their similarities and because they are complementary. At the end of this article, the objective is to define the two solutions, show their importance and present ways of using them in a complementary way with the objective of promoting greater value for organizations. Concluding at the end, the advantages that data analysis brings to companies. To achieve the objective of the article, articles, books, use cases and other content on the subject were used.
Keywords: Data; Organizations; Big Data; Business Intelligence